2023
DOI: 10.1021/acs.jafc.3c01489
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterols Protect against Osteoporosis by Regulating Gut Microbiota

Xiangyu Xiao,
Jiaojiao Wang,
Yucheng Zhu
et al.

Abstract: Osteoporosis is increasingly prevalent worldwide, representing a major health burden. However, there is a lack of nutritional strategies for osteoporotic therapy. Phytosterols, as natural bioactive compounds, have the potential to alleviate osteoporosis. In this study, a glucocorticoid-induced osteoporosis mouse model and treatment with low and high concentrations of phytosterols for 4 weeks were established. The results demonstrated that compared to the control group, low-concentration phytosterols (LP) (0.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
(77 reference statements)
1
0
0
Order By: Relevance
“…Meanwhile, beans are a good source of plant protein and proteins intake is positively associated with BMD and negatively related with osteoporosis regardless of protein source ( 51 53 ). Our results additionally demonstrated the beneficial effect of higher refined-grains score and lower refined-grains intake, and this may be attributed to the fact that refined grains are known to contain fewer vitamins, minerals, and phytosterols that are important for bone health and protection against osteoporosis ( 54 ). Furthermore, refined grains were found to decrease BMD by modulating osteoprotegerin and receptor activator of nuclear factor kappa B (NF-κB) in male rats ( 55 ).…”
Section: Discussionsupporting
confidence: 55%
“…Meanwhile, beans are a good source of plant protein and proteins intake is positively associated with BMD and negatively related with osteoporosis regardless of protein source ( 51 53 ). Our results additionally demonstrated the beneficial effect of higher refined-grains score and lower refined-grains intake, and this may be attributed to the fact that refined grains are known to contain fewer vitamins, minerals, and phytosterols that are important for bone health and protection against osteoporosis ( 54 ). Furthermore, refined grains were found to decrease BMD by modulating osteoprotegerin and receptor activator of nuclear factor kappa B (NF-κB) in male rats ( 55 ).…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, the depletion of the butyrate-producing Firmicutes bacterium Fusicatenibacter in OS patients could produce a beneficial effect on maintaining the stability of the intestinal lumen environment ( Tian et al., 2023 ). Ruminococcus was regarded as a beneficial bacterium related to the prevention of osteoporosis in studies focusing on the anti-osteoporosis mechanism of active ingredients ( Han et al., 2023 ; Xiao et al., 2023 ). To the best of our knowledge, Agathobacter has not been reported to be associated with osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research suggests a crucial role for gut microbiota in the development of osteoporosis. Xiao, XY et al [4] in a mouse experiment, found that phytosterols regulate gut microbiota to increase bone mass, exerting an antiosteoporotic effect. Wang, JH et al [5] conducted a diversity analysis of gut microbiota in osteoporosis and osteopenia patients, identifying statistically signi cant differences compared to a normal population, indicating that gut microbiota may be a critical factor in osteoporosis development.…”
Section: Introductionmentioning
confidence: 99%